Selection Criteria for Web-Based Resources in a Science and Technology Library Collection - Robert B. McGeachin (Issues in Science and Technology Librarianship)
This article discusses reasons to include Internet-based resources in a science and technology library collection. In addition to the normal collection development criteria for print materials, many additional factors unique to electronic resources are examined. These topics include: additional hardware and software requirements, user access regulation, funding the cost of Internet materials, user education and assistance, stability of Internet location, long term access, product licensing, cataloging of Internet materials, and delays in access due to heavy Internet traffic.